ANALISIS INVESTASI REKSADANA DAN LABA BUMN TERHADAP HARGA SAHAM BUMN DI BURSA EFEK INDONESIA - Bryan Mehaga Sebayang; Raina Linda Sari (Ekonomi dan Keuangan, 2015)
This research aims to analyze the mutual funds invesment and SOE profit to SOE share price in Indonesia Stock Exchange. Later in the formulation of the problem can be divided into two, namely the influence of investment funds to the stock price of SOEs in Indonesia Stock Exchange and how the influence of SOE profits on share price of SOEs in Indonesia Stock Exchange. This study uses panel data which combines time series, that is quartal data from 2009 to 2013, and a cross section of 14 state-owned companies that meet the criteria. The analyis and processing of data uses descriptive analysis and panel regression by using Eviews. In the descriptive analysis is descriptive simple. In the panel data regression analysis, the method used is the method of Pooled Least Square (PLS), Fixed Effect Model (FEM), Random Effect Model (REM) and then determined the most appropriate model using the Hausman test and gained Fixed Effect Model (FEM) is a model the most appropriate. The result of reseach shows there is a positive effect of mutual funds investment to SOE share price in Indonesia Stock Exchange and positive effect from SOE profit to SOE share price in Indonesia Stock Exchange.Keywords: SOE Profit, Mutual Funds Investment, SOE Share Prices, SOEs.